2022
DOI: 10.1002/eat.23711
|View full text |Cite
|
Sign up to set email alerts
|

Estimated prevalence of eating disorders in Malaysia based on a diagnostic screen

Abstract: Eating disorders (EDs) are debilitating health conditions and common across cultures. Recent reports suggest that about 14.0% of university students in Malaysia are at risk for developing an ED, and that prevalence may differ by ethnicity and gender. However, less is known about the prevalence of EDs in nonuniversity populations. Objective The current study seeks to (1) estimate the prevalence of EDs and ED risk status among adults in Malaysia using an established diagnostic screen; (2) examine gender and ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Their rise is probably connected with industrialization and urbanization. In Malaysia, over 50% of participants screened positive for an eating disorder or were identified as being at risk for developing an eating disorder [39 ▪ ]. In Singapore, 43% of participants screened positive for eating disorders, and one-fifth were identified as at high risk of developing an eating disorder [40 ▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Their rise is probably connected with industrialization and urbanization. In Malaysia, over 50% of participants screened positive for an eating disorder or were identified as being at risk for developing an eating disorder [39 ▪ ]. In Singapore, 43% of participants screened positive for eating disorders, and one-fifth were identified as at high risk of developing an eating disorder [40 ▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Whilst the vast majority of research on the epidemiology of ARFID has focussed on child and adolescent populations, a number of studies with adult samples have been published in recent years. Estimates of the prevalence of ARFID using population-based surveys or screening tools ranged from 0.3% to 4.8% in general adult populations across different countries from Oceania, North America, South-East Asia, or Europe (Fitzsimmons-Craft, Balantekin, Graham, Smolar, Park, Mysko, Funk, Taylor, Wilfley;Chua et al, 2021;Hilbert et al, 2021;Chua et al, 2022;Hay et al, 2017). In clinical populations, a retrospective chart review of Japanese women with feeding and eating disorders aged 15-40 years revealed that 11% of the sample met DSM-5 criteria for ARFID (Nakai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although limited, the three month prevalence estimates of ARFID in an adult Australian population (0.3%) and prevalence of severe fussy eating in a NZ child birth cohort (1.9%) are comparable to the wide range of international prevalence estimates of ARFID in non-clinical populations (0.5–1.3% in children [ 3 , 62 ], and 4.1–4.8% in adults [ 10 , 63 ]).…”
Section: Discussionmentioning
confidence: 85%